High-adsorption material based on metal organic framework and preparation method of high-adsorption material
By combining modification of metal organic framework materials and loading technology, a high adsorption material was prepared, which solved the shortcomings of existing MOFs materials in water molecules competitive adsorption and structural stability, and achieved efficient adsorption and good regeneration performance of high concentration organic gases.
Patent Information
- Application Number
- CN202510200379.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-18
AI Technical Summary
The existing metal organic framework (MOFs) materials have insufficient competitive adsorption and structural stability of water molecules in industrially emitted organic waste gases, resulting in poor results in practical applications.
A highly adsorbent material was prepared by modifying the aminated metal organic framework polymer microspheres using propionic anhydride, introducing -propyl organic groups, and combining porous polyacrylate microsphere loading technology. The material improves its adsorption ability and hydrophobic properties to organic gases by doping copper ions and modified organic groups.
It significantly improves the hydrophobicity, adsorption ability and regeneration properties of the material, can effectively adsorb high concentrations and high temperature organic gases, and shows good stability and reusability under industrial conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and in particular to a high adsorption material based on a metal organic framework and a preparation method thereof. Background Art
[0002] Volatile organic compounds (VOCs) are organic compounds that can react with NO in the atmosphere. X 、SO X , NH3, and generate organic compounds of photochemical pollutants, fine particulate matter (PM2.5) and greenhouse gases, which mainly come from gas emissions from industries such as petrochemicals, leather making, spray printing, and automobile exhaust. In recent years, with the rapid development of my country's industry and the promotion of urbanization, the emission of VOCs has increased rapidly. Most of these VOCs are toxic and can cause irreversible damage to the human body and the environment. Therefore, it is urgent to control VOCs and reduce VOCs emissions.
[0003] At present, the treatment technology of VOCs mainly relies on adsorption treatment. The key to this method is the adsorbent used. Traditional adsorbents include activated carbon, molecular sieves, silica gel, etc., but their adsorption capacity for VOCs is generally low and they are not suitable for high-concentration, high-temperature organic waste gas. The adsorption material has a short lifespan and there are residues in the replaced adsorption material, which can easily cause secondary pollution. Metal organic frameworks (MOFs) are porous materials with a periodic network structure formed by self-assembly of metal ions and organic ligands through coordination. They not only have a crystalline structure with regular pores similar to zeolite molecular sieves, but also have a higher specific surface area and porosity than traditional porous materials. These characteristics make them have great potential in VOCs adsorption.
[0004] The adsorption mechanism of MOFs on VOCs includes open metal sites, π-complexation effect, hydrogen bonding, electrostatic effects, etc. Although MOFs have great application prospects in the adsorption of VOCs, their practical applications are limited by the insufficient force provided by their skeletons, poor chemical stability, and sensitivity to water molecules. When industrial VOCs are discharged, they carry about 10% water vapor. These water molecules not only have a competitive adsorption relationship with organic molecules, but also destroy the crystallinity of MOFs, causing the hydrolysis of metal-organic bonds, and ultimately leading to structural collapse. Therefore, constructing highly adsorbable and highly hydrophobic MOFs is of great significance to promote VOCs governance. Summary of the invention
[0005] The purpose of the present invention is to provide a high adsorption material based on a metal organic framework and a preparation method thereof, so as to solve the problem that the hydrophobicity of MOFs is not good enough and cannot be applied to industrial production.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a high adsorption material based on a metal organic framework, specifically comprising: The propionic anhydride was dissolved in chloroform, stirred evenly and then the amino metal organic framework polymer microspheres were added, and then the temperature was raised to 50-60°C under negative pressure and refluxed for 5-7 hours. After the reaction was completed, the mixture was cooled, filtered, washed with chloroform and ethanol, and dried to obtain a high adsorption material based on a metal organic framework.
[0007] As a limitation of the present invention, the mass ratio of the propionic anhydride to the amino metal organic framework polymer is 1:(5-15).
[0008] As a limitation of the present invention, the preparation method of the amino metal organic framework polymer is: The metal nitrate is added to N,N-dimethylformamide, stirred evenly, and 2-aminoterephthalic acid is added after ultrasonic dissolution, and the temperature is raised to 70-90°C, and stirring is continued to form an amino metal organic framework precursor solution. After the porous polyacrylate microspheres are added to the amino metal organic framework precursor solution, they are fully immersed under negative pressure and then transferred to a polytetrafluoroethylene reactor together, and the temperature is raised to 140-160°C for reaction for 20-28 hours. After the reaction is completed, the solution is cooled, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried to obtain an amino metal organic framework polymer.
[0009] As a limitation of the present invention, the metal nitrate is composed of chromium nitrate nonahydrate and copper nitrate nonahydrate, and the mass ratio of chromium nitrate nonahydrate to copper nitrate nonahydrate is (7-9):(1-3).
[0010] As a limitation of the present invention, the mass ratio of the metal nitrate, 2-aminoterephthalic acid and porous polyacrylate microspheres is (14-18):(3.5-3.7):(1-3).
[0011] As a limitation of the present invention, the preparation method of the porous polyacrylate microspheres is: Add tert-butyl acrylate, trimethylolpropane triacrylate, tert-butyl methacrylate and emulsifier to toluene in sequence, stir evenly, then add benzoyl peroxide, slowly add deionized water at 6000-7000 rpm, continue stirring for 3-5 minutes, add N,N-dimethylbenzamide after 3-5 minutes, continue stirring evenly to obtain acrylate emulsion; Deionized water, polyvinyl alcohol and ammonium persulfate were mixed and stirred evenly. Acrylic emulsion was slowly added at 60-70°C and 200-300rpm. Stirring was continued for 5-15min. After the reaction was completed, the mixture was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
[0012] As a limitation of the present invention, the acrylic emulsion includes, by mass, 2 to 3 parts of tert-butyl acrylate, 1.5 to 2.5 parts of trimethylolpropane triacrylate, 0.5 to 1 part of tert-butyl methacrylate, 0.3 to 0.5 parts of emulsifier, and 0.1 to 0.2 parts of benzoyl peroxide.
[0013] As a limitation of the present invention, the mass ratio of the polyvinyl alcohol to ammonium persulfate is (1-3):(2-4).
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts copper nitrate nonahydrate and chromium nitrate nonahydrate to provide metal ions, aminoterephthalic acid as an organic ligand, and synthesizes an organic metal skeleton doped with copper ions. After being doped with copper ions, active sites on the organic metal skeleton are increased, and the adsorption capacity of the organic gas is enhanced without changing the crystal structure, and the saturated adsorption capacity of the organic gas is improved. Propionic anhydride is used to modify the amino group on the organic metal skeleton, and an organic group-propyl group is introduced into the organic metal skeleton, which improves the hydrophobic property of the material and enhances the adsorption capacity of the organic gas.
[0015] The present invention uses porous polyacrylate microspheres to load the modified organic metal skeleton, which not only improves the hydrophobicity, mechanical strength and wear resistance of the material, but also avoids the shortcomings of the organic metal skeleton of the powder piling up to reduce the adsorption effect, directly filling the bed layer to cause excessive bed pressure drop, and the powder following the air flow to block the pipeline in actual production. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Emulsifier (Poloxamer 188, MW5800), polyvinyl alcohol (MW9000) Example 1: A method for preparing a high adsorption material based on a metal organic framework, specifically: Step 1: Prepare the acrylic emulsion 2.3 g of tert-butyl acrylate, 2.0 g of trimethylolpropane triacrylate, 0.7 g of tert-butyl methacrylate and 0.4 g of emulsifier were added to 3.9 g of toluene in sequence, and after stirring evenly, 0.1 g of benzoyl peroxide was added. At 7000 rpm, 15 g of deionized water was slowly added and stirring was continued for 4 min. After 4 min, 0.3 g of N, N-dimethylbenzamide was added and stirring was continued for 1 min to obtain an acrylate emulsion.
[0018] Step 2: Preparation of porous polyacrylate microspheres 150 g of deionized water, 0.3 g of polyvinyl alcohol and 0.2 g of ammonium persulfate were mixed and stirred evenly. At 65°C and 250 rpm, acrylic emulsion was slowly added and stirred for 10 min. After the reaction was completed, it was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
[0019] Step 3: Preparation of amino metal organic framework polymer microspheres 1.28g of chromium nitrate nonahydrate and 0.32g of copper nitrate nonahydrate were added to 5g of N,N-dimethylformamide, stirred evenly, and 0.36g of 2-aminoterephthalic acid was added after ultrasonic dissolution. The temperature was raised to 80°C and stirred continuously to form an amino metal organic framework precursor solution. After 0.2g of porous polyacrylate microspheres were added to the amino metal organic framework precursor solution, vacuum treatment was performed, and under negative pressure conditions, the amino metal organic framework precursor solution entered into the porous polyacrylate microspheres. After being fully impregnated, they were transferred to a polytetrafluoroethylene reactor together, heated to 150°C for reaction for 24h, and after the reaction was completed, slowly cooled to room temperature, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried to obtain amino metal organic framework polymer microspheres.
[0020] Step 4: Preparation of highly adsorbent materials based on metal organic frameworks Dissolve 0.05 g of propionic anhydride in 12 mL of chloroform, stir evenly and add 0.5 g of amino metal organic framework polymer microspheres, then evacuate and heat to 55 °C under negative pressure for 6 hours. After the reaction, cool to room temperature, filter, wash with chloroform and ethanol, and dry to obtain a high adsorption material based on a metal organic framework.
[0021] Example 2: A method for preparing a high adsorption material based on a metal organic framework, specifically: Step 1: Prepare the acrylic emulsion 2.3 g of tert-butyl acrylate, 2.0 g of trimethylolpropane triacrylate, 0.7 g of tert-butyl methacrylate and 0.4 g of emulsifier were added to 3.9 g of toluene in sequence, and after stirring evenly, 0.1 g of benzoyl peroxide was added. At 7000 rpm, 15 g of deionized water was slowly added and stirring was continued for 4 min. After 4 min, 0.3 g of N, N-dimethylbenzamide was added and stirring was continued for 1 min to obtain an acrylate emulsion.
[0022] Step 2: Preparation of porous polyacrylate microspheres 150 g of deionized water, 0.3 g of polyvinyl alcohol and 0.2 g of ammonium persulfate were mixed and stirred evenly. At 65°C and 250 rpm, acrylic emulsion was slowly added and stirred for 10 min. After the reaction was completed, it was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
[0023] Step 3: Preparation of amino metal organic framework polymer microspheres 1.44 g of chromium nitrate nonahydrate and 0.16 g of copper nitrate nonahydrate were added to 5 g of N,N-dimethylformamide, stirred evenly, and 0.36 g of 2-aminoterephthalic acid was added after ultrasonic dissolution. The temperature was raised to 80°C and stirred continuously to form an amino metal organic framework precursor solution. After 0.2 g of porous polyacrylate microspheres were added to the amino metal organic framework precursor solution, vacuum treatment was performed, and under negative pressure conditions, the amino metal organic framework precursor solution entered into the porous polyacrylate microspheres. After being fully impregnated, they were transferred to a polytetrafluoroethylene reactor together, heated to 150°C for reaction for 24 hours, and after the reaction was completed, slowly cooled to room temperature, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried to obtain amino metal organic framework polymer microspheres.
[0024] Step 4: Preparation of highly adsorbent materials based on metal organic frameworks Dissolve 0.05 g of propionic anhydride in 12 mL of chloroform, stir evenly and add 0.5 g of amino metal organic framework polymer microspheres, then evacuate and heat to 55 °C under negative pressure for 6 hours. After the reaction, cool to room temperature, filter, wash with chloroform and ethanol, and dry to obtain a high adsorption material based on a metal organic framework.
[0025] Example 3: A method for preparing a high adsorption material based on a metal organic framework, specifically: Step 1: Prepare the acrylic emulsion 2.3 g of tert-butyl acrylate, 2.0 g of trimethylolpropane triacrylate, 0.7 g of tert-butyl methacrylate and 0.4 g of emulsifier were added to 3.9 g of toluene in sequence, and after stirring evenly, 0.1 g of benzoyl peroxide was added. At 7000 rpm, 15 g of deionized water was slowly added and stirring was continued for 4 min. After 4 min, 0.3 g of N, N-dimethylbenzamide was added and stirring was continued for 1 min to obtain an acrylate emulsion.
[0026] Step 2: Preparation of porous polyacrylate microspheres 150 g of deionized water, 0.3 g of polyvinyl alcohol and 0.2 g of ammonium persulfate were mixed and stirred evenly. At 65°C and 250 rpm, acrylic emulsion was slowly added and stirred for 10 min. After the reaction was completed, it was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
[0027] Step 3: Preparation of amino metal organic framework polymer microspheres 1.12g of chromium nitrate nonahydrate and 0.48g of copper nitrate nonahydrate were added to 5g of N,N-dimethylformamide, stirred evenly, and 0.36g of 2-aminoterephthalic acid was added after ultrasonic dissolution. The temperature was raised to 80°C and stirred continuously to form an amino metal organic framework precursor solution. After 0.2g of porous polyacrylate microspheres were added to the amino metal organic framework precursor solution, vacuum treatment was performed, and under negative pressure conditions, the amino metal organic framework precursor solution entered into the porous polyacrylate microspheres. After being fully impregnated, they were transferred to a polytetrafluoroethylene reactor together, heated to 150°C for reaction for 24h, and after the reaction was completed, slowly cooled to room temperature, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried to obtain amino metal organic framework polymer microspheres.
[0028] Step 4: Preparation of highly adsorbent materials based on metal organic frameworks Dissolve 0.05 g of propionic anhydride in 12 mL of chloroform, stir evenly and add 0.5 g of amino-loaded metal organic framework microspheres, then evacuate and heat to 55 °C under negative pressure for 6 h. After the reaction, cool to room temperature, filter, wash with chloroform and ethanol, and dry to obtain a high adsorption material based on a metal organic framework.
[0029] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below: Comparative Example 1: This comparative example relates to a method for preparing a high adsorption material based on a metal organic framework. The difference from Example 1 is that only chromium nitrate nonahydrate is used, and copper nitrate nonahydrate is not added. Specifically: Step 1: Prepare the acrylic emulsion 2.3 g of tert-butyl acrylate, 2.0 g of trimethylolpropane triacrylate, 0.7 g of tert-butyl methacrylate and 0.4 g of emulsifier were added to 3.9 g of toluene in sequence, and after stirring evenly, 0.1 g of benzoyl peroxide was added. At 7000 rpm, 15 g of deionized water was slowly added and stirring was continued for 4 min. After 4 min, 0.3 g of N, N-dimethylbenzamide was added and stirring was continued for 1 min to obtain an acrylate emulsion.
[0030] Step 2: Preparation of porous polyacrylate microspheres 150 g of deionized water, 0.3 g of polyvinyl alcohol and 0.2 g of ammonium persulfate were mixed and stirred evenly. At 65°C and 250 rpm, acrylic emulsion was slowly added and stirred for 10 min. After the reaction was completed, it was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
[0031] Step 3: Preparation of amino metal organic framework polymer microspheres 1.6 g of chromium nitrate nonahydrate was added to 5 g of N,N-dimethylformamide, stirred evenly, and 0.36 g of 2-aminoterephthalic acid was added after ultrasonic dissolution. The temperature was raised to 80°C and stirred continuously to form an amino metal organic framework precursor solution. 0.2 g of porous polyacrylate microspheres were added to the amino metal organic framework precursor solution, and then vacuum treatment was performed. Under negative pressure conditions, the amino metal organic framework precursor solution entered the porous polyacrylate microspheres. After sufficient immersion, the microspheres were transferred to a polytetrafluoroethylene reactor together, heated to 150°C and reacted for 24 hours. After the reaction was completed, the solution was slowly cooled to room temperature, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried to obtain amino metal organic framework polymer microspheres.
[0032] Step 4: Preparation of highly adsorbent materials based on metal organic frameworks Dissolve 0.05 g of propionic anhydride in 12 mL of chloroform, stir evenly and add 0.5 g of amino metal organic framework polymer microspheres, then evacuate and heat to 55 °C under negative pressure for 6 hours. After the reaction, cool to room temperature, filter, wash with chloroform and ethanol, and dry to obtain a high adsorption material based on a metal organic framework.
[0033] Comparative Example 2: This comparative example relates to a method for preparing a high adsorption material based on a metal organic framework. The difference from Example 1 is that propionic anhydride is not used to modify the amino metal organic framework polymer microspheres. Specifically: Step 1: Prepare the acrylic emulsion 2.3 g of tert-butyl acrylate, 2.0 g of trimethylolpropane triacrylate, 0.7 g of tert-butyl methacrylate and 0.4 g of emulsifier were added to 3.9 g of toluene in sequence, and after stirring evenly, 0.1 g of benzoyl peroxide was added. At 7000 rpm, 15 g of deionized water was slowly added and stirring was continued for 4 min. After 4 min, 0.3 g of N, N-dimethylbenzamide was added and stirring was continued for 1 min to obtain an acrylate emulsion.
[0034] Step 2: Preparation of porous polyacrylate microspheres 150 g of deionized water, 0.3 g of polyvinyl alcohol and 0.2 g of ammonium persulfate were mixed and stirred evenly. At 65°C and 250 rpm, acrylic emulsion was slowly added and stirred for 10 min. After the reaction was completed, it was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
[0035] Step 3: Preparation of highly adsorbent materials based on metal organic frameworks 1.28g of chromium nitrate nonahydrate and 0.32g of copper nitrate nonahydrate were added to 5g of N,N-dimethylformamide, stirred evenly, and 0.36g of 2-aminoterephthalic acid was added after ultrasonic dissolution. The temperature was raised to 80°C and stirred continuously to form an amino metal organic framework precursor solution. After 0.2g of porous polyacrylate microspheres were added to the amino metal organic framework precursor solution, vacuum treatment was performed, and under negative pressure conditions, the amino metal organic framework precursor solution entered into the porous polyacrylate microspheres. After being fully impregnated, they were transferred to a polytetrafluoroethylene reactor together, heated to 150°C for reaction for 24h, and after the reaction was completed, slowly cooled to room temperature, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried to obtain a high adsorption material based on a metal organic framework.
[0036] Comparative Example 3: This comparative example relates to a method for preparing a high adsorption material based on a metal organic framework. The difference from Example 1 is that porous polyacrylate microspheres are not used for loading. Specifically: Step 1: Preparation of aminated metal organic frameworks Add 1.28g of chromium nitrate nonahydrate and 0.32g of copper nitrate nonahydrate to 5g of N,N-dimethylformamide, stir evenly, add 0.36g of 2-aminoterephthalic acid after ultrasonic dissolution, heat to 80°C, stir continuously to form an amino metal organic framework precursor solution, transfer the amino metal organic framework precursor solution to a polytetrafluoroethylene reactor, heat to 150°C and react for 24h, slowly cool to room temperature after the reaction is completed, filter, wash with N,N-dimethylformamide and ethanol, and vacuum dry to obtain an amino metal organic framework.
[0037] Step 2: Preparation of highly adsorbent materials based on metal organic frameworks Dissolve 0.05 g of propionic anhydride in 12 mL of chloroform, stir evenly, add 0.5 g of amino metal organic framework, heat to 55 °C and reflux for 6 hours. After the reaction is completed, cool to room temperature, filter, wash with chloroform and ethanol, and dry to obtain a high adsorption material based on the metal organic framework.
[0038] Detection experiment: High adsorption materials for testing were prepared according to the preparation methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.
[0039] Hydrophobicity test: The prepared high adsorption material is crushed and ground into powder, and then pressed into a sample for the experiment using a tablet press. After the sample is placed on the stage of the measuring instrument, deionized water is dropped on the sample using a syringe, and the hydrophobicity of the material is measured using a water contact angle meter.
[0040] VOCs dynamic adsorption test: In order to simulate the application of the adsorbent under actual working conditions, the test was carried out in a small fixed bed reactor in a dark environment. Before the test, the sample was placed in a vacuum drying oven at 150°C for 3h. After the activation was completed, 1g of the activated sample was taken and placed in a cylindrical quartz tube adsorber (8×500mm, wall thickness 1mm). High-purity nitrogen was used as carrier gas and protective gas. The nitrogen as carrier gas was passed into the toluene solution, and toluene was taken out by bubbling, and mixed with nitrogen as protective gas. After forming a mixed gas, it was merged with oxygen and passed into the quartz tube adsorber together. The gas flow rate of the entire reaction was adjusted to 400mL / min by a flowmeter, the concentration ratio of oxygen to nitrogen was controlled at 2:8, the toluene concentration was controlled at 300ppm, and the reactor temperature was controlled at 25°C. A portable VOCs detector was used to monitor the outlet concentration of toluene at the quartz tube adsorber position in real time, and the saturated adsorption capacity of each sample was calculated.
[0041] Regeneration performance test: In the VOCs dynamic adsorption test, when the outlet concentration of toluene is close to the inlet concentration and stable, it is considered that the adsorbent has been saturated with adsorption. High-purity nitrogen is used as the purge gas and connected to the quartz tube adsorber. The nitrogen flow rate is adjusted to 400mL / min and the adsorber regeneration temperature is 150°C. A portable VOCs detector is used to monitor the outlet concentration of toluene at the quartz tube adsorber in real time until the outlet concentration is 0. It is considered that the adsorbent has been regenerated. The VOCs adsorption test is carried out again to measure the saturated adsorption capacity of each sample after regeneration and compare it with the original saturated adsorption capacity.
[0042] Conclusion: It can be seen from the test data that compared with the high adsorption materials prepared by the methods of Comparative Examples 1, 2 and 3, the high adsorption materials prepared by the method of Example 1 have improved hydrophobicity, adsorption capacity for organic gases and regeneration performance of the adsorption materials. The high adsorption material based on the organometallic framework prepared by the present invention has good adsorption capacity and regeneration performance, and also has good hydrophobicity, and is expected to be used for the treatment of VOCs in actual production.
[0043] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a high adsorption material based on a metal organic framework, characterized in that: Specifically: Dissolve propionic anhydride in chloroform, stir evenly and add amino organic metal framework polymer microspheres, then heat to 50-60°C under negative pressure and reflux for 5-7 hours. After the reaction is completed, cool, filter, wash with chloroform and ethanol, and dry to obtain a high adsorption material based on a metal organic framework.
2. The method for preparing a high adsorption material based on a metal organic framework according to claim 1, characterized in that: The mass ratio of propionic anhydride to amino metal organic framework polymer microspheres is 1:(5-15).
3. The method for preparing a high adsorption material based on a metal organic framework according to claim 1, characterized in that: The preparation method of amino metal organic framework polymer microspheres is as follows: Add metal nitrate to N,N-dimethylformamide, stir evenly, add 2-aminoterephthalic acid after ultrasonic dissolution, heat to 70-90°C, stir continuously to form an amino metal organic framework precursor solution, add porous polyacrylate microspheres to the amino metal organic framework precursor solution, and then transfer them to a polytetrafluoroethylene reactor under negative pressure after sufficient immersion, heat to 140-160°C and react for 20-28h. After the reaction is completed, cool, filter, wash with N,N-dimethylformamide and ethanol, and vacuum dry to obtain amino metal organic framework polymer microspheres.
4. The method for preparing a high adsorption material based on a metal organic framework according to claim 3, characterized in that: The metal nitrate is composed of chromium nitrate nonahydrate and copper nitrate nonahydrate, and the mass ratio of chromium nitrate nonahydrate to copper nitrate nonahydrate is (7-9):(1-3).
5. The method for preparing a high adsorption material based on a metal organic framework according to claim 3, characterized in that: The mass ratio of metal nitrate, 2-aminoterephthalic acid and porous polyacrylate microspheres is (14-18):(3.5-3.7):(1-3).
6. The method for preparing a high adsorption material based on a metal organic framework according to claim 3, characterized in that: The preparation method of porous polyacrylate microspheres is as follows: Add tert-butyl acrylate, trimethylolpropane triacrylate, tert-butyl methacrylate and emulsifier to toluene in sequence, stir evenly, then add benzoyl peroxide, slowly add deionized water at 6000-7000 rpm, continue stirring for 3-5 minutes, add N,N-dimethylbenzamide after 3-5 minutes, continue stirring evenly to obtain acrylate emulsion; Deionized water, polyvinyl alcohol and ammonium persulfate were mixed and stirred evenly. Acrylic emulsion was slowly added at 60-70°C and 200-300rpm. Stirring was continued for 5-15min. After the reaction was completed, the mixture was filtered, washed with methanol and dried to obtain porous polyacrylate microspheres.
7. The method for preparing a high adsorption material based on a metal organic framework according to claim 6, characterized in that: Calculated by mass, the acrylic emulsion includes 2 to 3 parts of tert-butyl acrylate, 1.5 to 2.5 parts of trimethylolpropane triacrylate, 0.5 to 1 part of tert-butyl methacrylate, 0.3 to 0.5 parts of emulsifier, and 0.1 to 0.2 parts of benzoyl peroxide.
8. The method for preparing a high adsorption material based on a metal organic framework according to claim 6, characterized in that: The mass ratio of polyvinyl alcohol to ammonium persulfate is (1-3):(2-4).